Avaliação do perfil de ativação de monócitos na ancilostomíase humana - Livia Silva Araujo Passos (2013)
The hookworm is one of the most prevalent parasitic chronic diseases, infecting an estimated 740 million people in tropical and subtropical regions of the world. A robust but ineffective immune response against the parasite allows it to survive in their host for several years, which is a strong indicator of immune evasion by the parasite. However, due to lack of studies about the cellular immune response in experimental and human hookworm infected, the evasion mechanisms triggered by the parasite, including the profile of activation of monocytes in infection, has not been addressed. In the present study, we evaluated by immunophenotyping and by the expression of some genes associated with different profiles of monocyte activation in the natural infection hookworms. Moreover, we verified the ability of parasite antigens in converting the phenotype profile of monocytes from controls individuals for resembling profile to that seen in monocytes infected individuals living in endemic areas. Our results showed that hookworm infected individuals have a higher frequency of monocytes when compared to controls and those monocytes have regulatory characteristics evidenced mainly by the high expression of IL-10. Furthermore, these individuals have elevated expression of nitric oxide synthase (iNOS) associated with the increased expression of IgE receptors low affinity (CD23) and low expression of IL-12. The evaluation of molecules associated with alternative activation profile in these monocytes such as mannose receptors (CD206), expression of IL-4 and arginase-1 showed no differences compared with the control group. Such data together, enabling us to conclude that monocytes from individuals naturally infected have predominantly regulatory characteristics and therefore may contribute to the prolonged survival of the parasite in the host organism, since these cells may contribute to the modulation of their immune response.